Bricks to Clicks : Students’ Engagement in E-Learning during the COVID-19 Pandemic - Donnie, Adams; Chuah, Kee Man; Ahmed, Mohamed; Bambang, Sumintono (USM Press, 2021)
The COVID-19 pandemic has forced higher education institutions to execute mitigation efforts such as an e-learning mode of instruction to reduce the impact on pedagogical activities. These challenges have raised concerns on students’ engagement in e-learning as students are at risk of falling behind in education. However, there is little empirical research focusing on students’ engagement in e-learning experiences. The purpose of this study is to investigate students’ engagement in e-learning as well as specifically assess their engagement based on gender, age, ethnicity, level of education and field of study in a Malaysian public higher education institution. This study used a non-experimental quantitative research design. Data were collected from a sample of 281 students using the Blended Learning Engagement Questionnaire©. WINSTEPS Rasch model measurement software was used to determine the reliability and validity of the research instrument. Subsequently, Differential item functioning (DIF) was conducted to assess students’ engagement in e-learning as well as specifically assessing student’s demographic factors such as gender, age, ethnicity, level of education and field of study. Findings indicate students have high levels of behavioural engagement as compared with cognitive and emotional engagement in e-learning. Further analysis indicated there were differences in students’ engagement based on demographic factors such as gender, age, and field of study. This study provides insight into students’ engagement in e-learning that will help lecturers to reflect on their own teaching practices. Implications and recommendations for future research are presented.